Rethinking the “Necessity” in Necessity Entrepreneurship - O’Donnell, Philip; O’Gorman, Colm; Clinton, Eric (Academy of Management Review, 2021)
Original paper: John C. Dencker, Sophie Bacq, Marc Gruber, and Melvin Haas, Reconceptualizing necessity entrepreneurship: A contextualized framework of entrepreneurial processes under the condition of basic needs, https://doi.org/10.5465/amr.2017.0471